Benefit Incidence Analysis of Education Sector in Divided Region in North Sulawesi - Fasnie Rorong, Ita Pingkan; Setyo Tri Wahyudi, Candra Fajri Ananda, Susilo Susilo, (Opción, 2019)
This research was conducted to understand the impact on the economic development, fiscal capacity, and public service in South Minahasa District and Tomohon City by Benefit Incidence Analysis (BIA), for helping the government to evaluate the program. It showed that the benefit of education expenditure in South Minahasa District on 2015 has mostly benefited. The next revenue group benefiting from most of the education expenditures is the third, or middle, revenue quintile, and it is similar to Tomohon City. In conclusion, the education expenditure benefit at South Minahasa District in 2015 is enjoyed mostly by the first and second revenue quintiles